Disruption of protein complexes containing protein phosphatase 2B and Munc18c reduces the secretion of von Willebrand factor from endothelial cells. (13th April 2017) - Da, Q.; Shaw, T.; Pradhan, S.; Roche, P. A.; Cruz, M. A.; Vijayan, K. Vinod
Abstract : Essentials Endothelial secretion of von Willebrand factor (VWF) promotes inflammation and thrombosis. We studied the role of protein phosphatase 2B (PP2B) and Munc18c protein complex in VWF secretion. Disruption of PP2B‐Munc18c complex in endothelial cells reduced agonist‐induced VWF secretion. PP2B‐Munc18c complex represents a potential target for thrombotic and inflammatory conditions. Summary: Background: Aberrant secretion of von Willebrand factor (VWF) from endothelial cells contributes to inflammation and vascular thrombosis. Agonist‐induced VWF secretion is facilitated by protein kinase and phosphatase‐mediated signaling. Although the catalytic subunit of protein phosphatase 2B (PP2B‐Aα) is targeted to the secretory machinery via an interaction with the vesicle trafficking protein Munc18c in endothelial cells, the functional relevance of this phosphatase complex is unclear. Objective: To assess the contribution of the PP2B‐Aα–Munc18c complex to endothelial VWF secretion. Results: Here, we show that amino acids 120–130 of PP2B‐Aα are important to support an interaction with Munc18c. A synthetic myristylated cell‐permeable peptide, which is derived from amino acids 121–130 of PP2B‐Aα, disrupted endogenous PP2B‐Aα–Munc18c complexes in human umbilical vein endothelial cells, and decreased low‐dose histamine‐stimulated and thrombin‐stimulated VWF secretion. Conclusion: These studies indicate that PP2B‐Aα–Munc18c complex supports agonist‐induced VWF secretion, and suggest the potential of targeting this phosphatase complex in thrombotic and inflammatory conditions.